ANALISIS GANGUAN PERANGKAT HUBUNG BAGI TEGANGAN RENDAH PADA GARDU DISTRIBUSI DI PLN UP3 BEKASI - Hilman Azizi (Universitas Islam Lamongan, 2023)
This analysis focuses on device interference to connect low or short voltage (PHB-TR) at substation distribution and overcome it at PT PLN (Persero) UP3 Bekasi UID West Java. PHB-TR is an electrical device or equipment in the form of a connecting device made of conductive and non-conductive materials mounted on a frame or cabinet and equipped with electrical equipment and electrical safety and is part of a distribution substation on the low voltage side. The disturbances in the PHB-TR are usually caused by human error or environmental factors that refer to electrical devices and equipment. Therefore, based on the results of the analysis of PHB-TR disturbances in the distribution of substations at PLN UP3 Bekasi, they found disturbances and looked for solutions to these problems so that the distribution network installation operates reliably, performance operates well and the continuity of electric power services is maintained properly. activities that include a series of stages from planning, implementation, to controlling and evaluating PHB-TR installation maintenance work.